Allogeneic Hematopoietic Cell Transplantation for Patients With Deficiency of Adenosine Deaminase 2 (DADA2): Approaches, Obstacles and Special Considerations - Hashem, Hasan; Dimitrova, Dimana; Meyts, Isabelle (Frontiers in Immunology, 2022)
Deficiency of adenosine deaminase 2 (DADA2) is an inherited autosomal recessive disease characterized by autoinflammation (recurrent fever), vasculopathy (livedo racemosa, polyarteritis nodosa, lacunar ischemic strokes, and intracranial hemorrhages, end organ vasculitis), immunodeficiency, lymphoproliferation, immune cytopenias, and bone marrow failure. Allogeneic hematopoietic cell transplantation (HCT) is curative for DADA2 as it reverses the hematological, immune and vascular phenotype of DADA2. The primary goal of HCT in DADA2, like in other non-malignant diseases, is engraftment with the establishment of normal hematopoiesis and normal immune function. Strategies in selecting a preparative regimen should take into consideration the specific vulnerabilities to endothelial dysfunction and liver toxicity in DADA2 patients. Overcoming an increased risk of graft rejection while minimizing organ toxicity, graft-versus-host disease, and infections can be particularly challenging in DADA2 patients. This review will discuss approaches to HCT in DADA2 patients including disease-specific considerations, barriers to successful engraftment, post-HCT complications, and clinical outcomes of published patients with DADA2 who have undergone HCT to date.